Deficiency of peroxiredoxin 6 or inhibition of its phospholipase A2 activity impair the in vitro sperm fertilizing competence in mice. Issue 1 (December 2017) - Moawad, Adel; Fernandez, Maria; Scarlata, Eleonora; Dodia, Chandra; Feinstein, Sheldon; Fisher, Aron; O'Flaherty, Cristian
Abstract Prdx6 −/− male mice are subfertile, and the deficiency or inactivation of Peroxiredoxins (PRDXs) is associated with human male infertility. We elucidate the impact of the lack of PRDX6 or inhibition of its calcium-independent phospholipase A2 (Ca2+ -iPLA2 ) activity by MJ33 on fertilization competence of mouse spermatozoa. Sperm motility, viability, fertilization and blastocyst rates were lower inPrdx6 −/− spermatozoa than in C57BL/6J wild-type (WT) controls (p  ≤ 0.05). MJ33 inhibited the PRDX6 Ca2+ -iPLA2 activity and reduced these parameters in WT spermatozoa compared with controls (p  ≤ 0.05). Levels of lipid peroxidation and of superoxide anion (O2 ─ ) were higher inPrdx6 −/− than in WT spermatozoa (p  ≤ 0.05). MJ33 increased the levels of lipid peroxidation and mitochondrial O2 ─ production in treated versus non-treated WT spermatozoa. Acrosome reaction, binding to zona pellucida and fusion with the oolemma were lower inPrdx6 −/− capacitated spermatozoa than WT capacitated controls and lower in WT spermatozoa treated with the PRDX6 inhibitor. In conclusion, the inhibition of the PRDX6 Ca2+ -iPLA2 activity promotes an oxidative stress affecting viability, motility, and the ability of mouse spermatozoa to fertilize oocytes. Thus, PRDX6 has a critical role in the protection of the mouse spermatozoon against oxidative stress to assure fertilizing competence.